Recent Advances in Air Lasing: A Perspective from Quantum Coherence. Issue 11 (25th September 2019) - Yuan, Luqi; Liu, Yi; Yao, Jinping; Cheng, Ya
Abstract: The research topic of air lasing is of fundamental and practical importance, which has grown rapidly in the past decade. Air lasing, or a laser‐like emission from air species including atomic oxygen, atomic argon, atomic nitrogen, molecular nitrogen, and molecular nitrogen ions, has been investigated vastly in both experiment and theory. In this review, the basic concepts of air lasing are discussed and the crucial role of quantum coherence in the air‐lasing process is highlighted. As an exciting perspective, air lasing not only exhibits important fundamental physics such as superradiance, nonlinear effects, vibrational and rotational dynamics, but also shows potential practical implications toward remote sensing. Abstract : The research topic of air lasing is of fundamental and practical importance, which has grown rapidly in the past decade. In this review, the basic concepts of air lasing are discussed and the crucial role of quantum coherence in the air‐lasing process is highlighted, which exhibits both important fundamental physics and potential practical implications toward remote sensing.